Near‐infrared light‐responsive Nitric oxide microcarrier for multimodal tumor therapy - Danna Liang; Gaizhen Kuang; Xiang Chen; Jianhua Lu; Luoran Shang; Weijian Sun (Smart Medicine, 2023)
Abstract Nitric oxide (NO) has shown great potential in tumor therapy, and the development of a platform for precise and controllable NO release still needs to be explored. Herein, a microfluidic electrospray strategy is proposed for the fabrication of hydrogel microspheres encapsulating NO donors (S‐nitrosoglutathione, GSNO) together with black phosphorus (BP) and chemotherapeutic doxorubicin (DOX) as microcarriers for tumor therapy. Based on the excellent photothermal property of BP and thermal sensitivity of GSNO, the microcarriers exhibit a near‐infrared light (NIR)‐responsive NO release behavior. Besides, the photothermal performance of the microcarriers accelerates the release of DOX. All these contribute to the excellent tumor‐killing effect of the microcarriers by combining multiple therapeutic strategies including NO therapy, photothermal therapy, and chemotherapy. Moreover, it was demonstrated that the NIR‐responsive NO delivery microcarriers could significantly inhibit tumor growth without apparent side effects in vivo. Therefore, it is believed that the novel NIR‐responsive NO microcarriers are promising candidates in clinical tumor therapy applications.